Tinjauan Yuridis Status Anak Yang Lahir Dari Perkawinan Campuran Antara Warga Negara Asing (WNA) Dengan Warga Negara Indonesia (WNI) - Angga Dimas Pratama; Wiwiek Wahyuningsih (Fakultas Hukum Universitas Mataram, 2023)
This study aims to determine the marital status held abroad between Foreign Citizens (WNA) and Indonesian Citizens (WNI) and to determine the citizenship status of children born from mixed marriages. This research uses normative legal research methods. The results of the study concluded that marriages held abroad between Foreign Citizens (WNA) and Indonesian Citizens (WNI) marriages are valid if they do not violate the legal provisions of Singapore or the country where the marriage is held. Children born from such mixed marriages can choose their own nationality after the age of 18 because they are considered legally capable in accordance with the citizenship law.